Edutainment as a Strategy for Parental Discussion With Israeli Children: The Potential of a Children's Play in Preventing Sexual Abuse. Issue 5 (4th July 2017) - Gesser-Edelsburg, Anat; Fridman, Talia; Lev-Wiesel, Rachel
ABSTRACT: Edutainment is a communication strategy to influence attitudes and behaviors through the use of the media. Through the children's play "Yael Learns to Take Care of Her Body, " designed for joint viewing by children aged 5–8 and their parents, sexual abuse is raised. This qualitative study findings indicate that parents from low socioeconomic subgroups from the secular sector reported that their awareness had been raised by viewing the play and that they received tools for holding a conversation. Conversely, parents from high socioeconomic subgroups in the secular sector and parents from the national-religious sector were more ambivalent regarding the play's effectiveness. In order to make the conversation meaningful, the play has to tailor different messages to different audiences. A single program is not enough but should be part of a series of customized intervention programs for different subpopulations and separate programs for parents and children accompanied by professionals.